Horizontal Well Cleanup Operation using Foam in Different Coiled Tubing/Annulus Diameter Ratios - Khan, Javed (2013)
Well cleanup operation for large diameter well with low bottomhole pressure is problematic and common cleanout fluids are not effective as a circulation fluid due to severe pressure losses and low suspension capability. So, It is required to analyze a fluid which can suspend the solid particles even at low annular velocities and efficiently clean the wellbore. Recently, the use of foam as cleaning agent has become more popular due to its low density and high viscosity which are desirable in many underbalanced operations. This study is focused to analyze the coil tubing fill cleanout with foam in horizontal annulus. The objective of this paper is to investigate the effect of foam quality and velocity on fill concentration during horizontal wellbore cleanup operation at different CT/Annulus diametric ratios using Herschel Buckley viscosity model. Results showed that foam quality and velocity are the deciding factors for the fill transport. Present study also showed that for all size of fill particles, lower foam quality removes fill more efficiently than higher foam quality. It is noticed that diametric ratio has high effect on particle removal when foam quality is 70 %. Surprisingly, it is found that the effect of diametric ratio on fill concentration decreases when foam quality is 90%.